PERONEAL NERVE PALSY - Vely Eva Meria; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Peroneal nerve palsy is a disorder caused by interference with the peroneal nerve. Usually, a drop foot is seen in patients who have peroneal nerve palsy. Basically, the causes of peroneal nerve palsy are multifactorial. Trauma, compression of the nerve, systemic disease, ischemia, and idiopathy are factors that cause peroneal nerve palsy. Management of peroneal nerve palsy can be done non-operatively or operatively, depending on the cause and severity.